Functional insights into pathogen biology from 3D electron microscopy - Cyrklaff, Marek; Frischknecht, Friedrich; Kudryashev, Mikhail (FEMS microbiology reviews, 2017)
In recent years, novel imaging approaches revolutionised our understanding of the cellular and molecular biology of microorganisms. These include advances in fluorescent probes, dynamic live cell imaging, superresolution light and electron microscopy. Currently, a major transition in the experimental approach shifts electron microscopy studies from a complementary technique to a method of choice for structural and functional analysis. Here we review functional insights into the molecular architecture of viruses, bacteria and parasites as well as interactions with their respective host cells gained from studies using cryogenic electron tomography and related methodologies.